THE HAGUE CONVENTION: ADOPTION OF CHILDREN WHO ARE THE CITIZENS OF UKRAINE BY FOREIGNERS, REALITIES AND PROSPECTS - Mariana Shupiana (Vasyl Stefanyk Precarpathian National University, 2018)
The article defines the child's rights to the family education that are infringed under the conditions of the armed conflict, which increased the risk of the rise of orphanhood; the problem of adoption of children, who are the citizens of Ukraine, by foreigners is considered; advantages and disadvantages of such adoption are grounded; the Hague Convention "On Protection of Children and Cooperation in Respect of Inter-country Adoption" is analysed as an alternative to the solution of urgent problems of orphans; its main goals and prospects for children of the defined category are described.The main factors of the increase of internal migration are described, which led to the emergence of a new category of subjects of law - internally displaced persons who need urgent legal and social protection; the total number of registered internally displaced persons is specified; from them the number of children is determined in percentage terms; analyzed numerous violations of the rights of the child as a result of armed conflict in the East of Ukraine; describes the influence of internal migration on the development of the personality of a child of preschool age, especially if it is caused by war, as a result of which they become psychologically vulnerable; a brief analysis of the works of scientists from the specified intelligence was carried out; a number of articles of the Constitution of Ukraine on adoption of children are considered, in which the essence of the concept of "adoption" is disclosed, the conditions on which this process is carried out; the benefits of the Hague Convention are outlined; the principles of intercountry adoption are described with maximum consideration of the child's highest interests and observance of his rights and freedoms; describes the need for the adoption of this law for Ukrainian orphans, since joining the Convention introduces a procedure of verification potential adoptive parents, strengthens the control of adoptions abroad, and most importantly - enables the selection of a family for a child, relieves cooperation with countries whose citizens adopts  Ukrainian orphans, and as well as implementation of a mechanism for the real protection of the rights of each adopted child. Key words: anti-terrorist operation (ATO), internally displaced persons (IDPs), child's rights, upbringing, orphanhood, adoption, Convention "On the Rights of the Child", the Hague Convention "On Protection of Children and Cooperation in Respect of Inter-country Adoption".